Craig’s Contradictory Kalam: Trouble at the Moment of Creation - Wielenberg, Erik (TheoLogica: An International Journal for Philosophy of Religion and Philosophical Theology, 2021)
William Lane Craig’s much-discussed kalam cosmological argument for God’s existence is intended to provide support for a particular theistic explanation of the origin of the universe. I argue here that Craig’s theistic account of the origin of the universe entails two contradictions and hence should be rejected. The main contribution of the paper is the identification of some relatively straightforward but previously unrecognized problems in Craig’s hypothesis that the beginning of the universe was a temporal effect of a timeless personal cause.